Heidegger and the notion of prescience (Vorwissenschaft) as existential propaedeutic. (Part 1: The affection of the time) - Ordóñez García, José; Rüdinger, Kurt (Estudios de Filosofía, 2014)
This article deals with Heidegger’s notion of “prescience” (Vorwissenschaft), since it addresses knowing and thinking, and the incidence of existing features in their activities. First of all there is existence, which is the condition of possibility for any discipline. Time, which determines existence, will become the radical phenomenon that defines human being as Dasein. This is the term given to the subject of “prescience” and that we will translate as Extar, because we believe that this is the best way to understand thinking as characterized by finitude. Methodology. We have developed this work through a hermeneutic analysis of a genealogical nature based on the deployment of beingness. Results and conclusions. Time is not a scientific subject but a pre-scientific one and so it is a topic that concerns ontology rather than science. Not a physical phenomenon but an affective phenomenon.